2010
DOI: 10.1021/jf100449t
|View full text |Cite
|
Sign up to set email alerts
|

β-Carotene Isomerization Kinetics during Thermal Treatments of Carrot Puree

Abstract: The effect of thermal processing on the stability of beta-carotene in carrot puree was investigated in a broad temperature range (80-150 degrees C). Heat induced changes in the stability of beta-carotene resulting in the conversion into its cis-isomers until an equilibrium state was reached after prolonged heating. By using nonlinear one-step regression analysis, the overall isomerization of all-trans-beta-carotene and the formation of individual cis-isomers could be modeled with a fractional conversion model.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 27 publications
5
70
2
Order By: Relevance
“…Several studies report the decrease of all-trans-carotenoid and the concomitant increase in cis-isomers in vegetables subjected to thermal processes. [35][36][37] Our results suggest that the β-carotene decreased, whereas three cisisomers (15-cis-β-carotene, 13-cis-β-carotene and 9-cis-β-carotene) increased on prolonging the heating time, which is accelerated at higher microwave power. Therefore, suitable kinetics for carotenoids degradation was evaluated at different drying conditions to minimize its loss during drying.…”
Section: Degradation Kinetics Of β-Carotenementioning
confidence: 67%
“…Several studies report the decrease of all-trans-carotenoid and the concomitant increase in cis-isomers in vegetables subjected to thermal processes. [35][36][37] Our results suggest that the β-carotene decreased, whereas three cisisomers (15-cis-β-carotene, 13-cis-β-carotene and 9-cis-β-carotene) increased on prolonging the heating time, which is accelerated at higher microwave power. Therefore, suitable kinetics for carotenoids degradation was evaluated at different drying conditions to minimize its loss during drying.…”
Section: Degradation Kinetics Of β-Carotenementioning
confidence: 67%
“…It should be mentioned that a lot of different matrices, reaction media, and heating conditions were used in the different studies, which makes comparison of the obtained kinetic parameters difficult. In the kinetic study of Lemmens et al, 14 no oxidation was observed during thermal treatments of a carrot puree. The presence of oil, which is reported to act as a prooxidant, 21 can explain the observed differences between the carrot puree and the oil/carrot emulsion.…”
Section: ■ Introductionmentioning
confidence: 96%
“…As a consequence of expressing the data as contributions, the same kinetic parameters for the isomerization of all-E-β-carotene and for the formation of the sum of Zisomers were found. In the kinetic study of Lemmens et al, 14 in which carrot puree was thermally treated in the absence of oil, the reaction rate constant for thermal isomerization of all-E-β-carotene was much lower (0.035 min −1 compared to 0.099 min −1 ). In other words, the presence of oil accelerates the isomerization of β-carotene in carrot puree.…”
Section: ■ Introductionmentioning
confidence: 97%
“…Carrot is widely known as an effi cient source of carotenoids, especially of α-and β-carotene [Marx et al, 2003;Lemmens et al, 2010]. Not only is β-carotene known for its dyeing properties, but also for its health effects as a vitamin A precursor [Liu et al, 2010;Ramoneda et al, 2011].…”
Section: Introductionmentioning
confidence: 99%